Metabolomics studies of wild edible plants from Asteraceae family - Freitas, Jolindo Alencar (2020)
The plant family Asteraceae has important edible species, such as lettuce and chicory, which are widely cultivated around the world. Studies have demonstrated the importance to ingest wild and/or spontaneous plant species as salads or condiments, since they are sources of a wide variety of nutrients and secondary metabolites. Unfortunately, edible wild species ethnobotanical studies presented the use of species with chronic toxic compounds as pyrrolizidine alkaloids or unclear phytochemistry as E. fosbergii. This study aims to demonstrate, through LC-MS untargeted metabolomics analysis of plants, possible risks and advantages of including 11 Asteraceae wild edible leaves in population diet. Initially, E. fosbergii had its chemical profile studied, which showed for the first time in this species the occurrence of 28 compounds, including pyrrolizidine alkaloids, flavonoids and cinnamic acid derivatives. At second, E. fosbergii and E. sonchifolia had their metabolic profiling compared, revealing that E. fosbergii accumulates more pyrrolizidine alkaloids than E. sonchifolia, with main importance to emiline compound, present mainly in the first species. Then, the influence of soil composition and phenology were studied in both species, revealing the situation in which each plant accumulates certain classes of compounds. Apart from that, other nine species, including wild and domesticated crop species, had their LC-MS chemical profile compared. It was possible to observe that Bidens pilosa, Galinsoga parviflora, Acmella oleraceae samples had different chemical profiles from Cichorieae tribe samples. Cichorium intybus and Youngia japonica species had unique chemical profiles and were distinguished from other four species. Lactuca canadensis, Sonchus oleraceus and Cichorium endivia demonstrated a similar chemical profile among each other and with a few L. sativa samples. The main discriminant compounds were linked to the chemotaxonomic information of each tribe. In conclusion, these findings have not only demonstrated the importance of chemotaxonomy in Asteraceae but also presented that the studied wild edible species could bring a variety of secondary metabolites to population. At last, this study confirmed hypothesis of pyrrolizidine alkaloids presence in E. fosbergii, which is a risk to the population due to the toxicity of this class of secondary metabolites.